The Importance of Millet Cultivation and Aspects of Agro-Measures Related to Yield - Norkulovna, Ishankulova Gavkhar; Ne’mathon oglu, Tursunov Muhriddin (American Journal of Biology and Natural Sciences, 2026)
This article discusses the role of millet in agriculture, its biological characteristics, and the main aspects of its cultivation technology. The impact of agrotechnical measures on yield—such as tillage, seed preparation, sowing dates, fertilization, irrigation, and pest control—is also analyzed. According to the results of the study, it was found that the correct and timely implementation of agrotechnical measures significantly increases millet yield. The article is of practical importance for agricultural specialists and farmers.